SHAKESPEARE AND THE COCONUTS : on post-apartheid south african culture. - DISTILLER, NATASHA (WITS University Press, 2012)
In this book Natasha Distiller explores historic and contemporary uses of Shakespeare in South African society which illustrate the complexities of colonial and post-colonial realities as they relate to iconic Englishness. Beginning with Solomon Plaatje, the author looks at the development of an elite group educated in English and able to use Shakespeare to formulate South African works and South African identities. Refusing simple or easy answers, Distiller then explores the South African Shakespearian tradition postapartheid. Touching on the work of, amongst others, Can Themba, Bloke Modisane, Antony Sher, Stephen Francis, Rico Schacherl and Kopano Matlwa, and including the popular media as well as school textbooks, Shakespeare and the Coconuts engages with aspects of South Africau2019s complicated, painful, fascinating political and cultural worlds, and their intersections. Written in an accessible style to explain current cultural theory, Shakespeare and the Coconuts will be of interest to students, academics and the general interested reader.